Exploring the P. falciparum antigens associated with reduced risk of malaria in pregnancy - Mwai, Lucy; Musundi, Sebastian; Waweru, Harrison; Nagaoka, Hikaru; Limbua, Purity Gacheri; Tsuboi, Takafumi; Takashima, Eizo; Gitaka, Jesse; Kanoi, Bernard N. (Frontiers in Immunology, 2025)
Plasmodium falciparum infection in pregnancy leads to substantial maternal and infant morbidity and mortality. Such an infection may result in placental malaria (PM) due to P. falciparum-infected red blood cells adhering to the placenta via parasite-derived ligands. Despite the risk of infection being the same for women of all gravidities, the risk of poor birth outcomes is highest in primigravida women as they lack protective antibodies against placental malaria-associated parasites. Thus, understanding how specific P. falciparum antigens interact with the host’s immune system during the first and subsequent pregnancies may provide insights into the immunopathology of malaria and guide vaccine target prioritization. In this study, we assessed human antibody responses to 698 P. falciparum recombinant antigens derived from different antigen families among Kenyan primigravida and multigravida women. Consistent with existing literature, we observed high immunoreactivity across the different antigen families, with the number of antigens identified by sera from pregnant women increasing with gravidity. Antibody response analysis selected 3 antigens: PF3D7_1301800 (SURFIN 13.1), PF3D7_0424400 (SURFIN 4.2), and PF3D7_1252100 (rhoptry neck antigen 3 domain) as statistically significant in multigravida. While all five VAR2CSA domains were immunoreactive with seroprevalence of 42 - 62% and correlated with the selected antigens, which suggests co-acquisition, none had statistical significance in association with gravidity. Thus, although further characterization of the selected antigens will be required, this study may provide insights into targets that could be prioritized for vaccine development to reduce risks associated with malaria in pregnancy.